Ethnocultural and Sex Characteristics of Patients Attending a Tertiary Care Pain Clinic in Toronto, Ontario - Angela Mailis-Gagnon; Balaji Yegneswaran; Keith Nicholson; SF Lakha; Marios Papagapiou; Amanda J Steiman; Danny Ng; Tea Cohodarevic; Margarita Umana; Mateusz Zurowski (Pain Research and Management)
BACKGROUND: Ethnocultural factors and sex may greatly affect pain perception and expression. Emerging literature is also documenting racial and ethnic differences in pain access and care.